Development and Evaluation of Low Phytic Acid Soybean by siRNA Triggered Seed Specific Silencing of Inositol Polyphosphate 6-/3-/5-Kinase Gene - Punjabi, Mansi; Bharadvaja, Navneeta; Jolly, Monica; Dahuja, Anil; Sachdev, Archana (Frontiers in Plant Science, 2018)
Soybean is one of the leading oilseed crop in the world and is showing a remarkable surge in its utilization in formulating animal feeds and supplements. Its dietary consumption however is incongruent with its existing industrial demand due to the presence of anti-nutritional factors in sufficiently large amounts. Phytic acid in particular raises concern as it causes a concomitant loss of indigestible complexed minerals and charged proteins in the waste and results in reduced mineral bioavailability in both livestock and humans. Reducing the seed phytate level thus seems indispensable to overcome the nutritional menace associated with soy grain consumption. In order to concieve our objective we designed and expressed a inositol polyphosphate 6-/3-/5-kinase gene-specific RNAi construct in the seeds of Pusa-16 soybean cultivar. We subsequently conducted a genotypic, phenotypic and biochemical analysis of the developed putative transgenic populations and found very low phytic acid levels, moderate accumulation of inorganic phosphate and elevated mineral content in some lines. These low phytic acid lines did not show any reduction in seedling emergence and displayed an overall good agronomic performance.